The influence of dietary nutrients on intrahepatocellular lipid metabolism - Cross, E (2023)
Pathological accumulation of intrahepatocellular triacylglycerol (IHTAG) is the first stage of metabolic dysfunction-associated steatotic liver disease (MASLD). Intervention studies have shown that diets rich in saturated fatty acids (SFA) compared to unsaturated fatty acids (UNSFA) increase IHTAG accumulation to a greater extent. Studying the underlying metabolic mechanisms driving these differences in IHTAG accumulation in vivo in humans remains challenging therefore, in vitro cellular models which recapitulate the effects of dietary alterations in hepatic metabolism are needed.